Long-Term Outcomes of Dartos-Augmented Snodgrass Repair in Distal and Mid Hypospadias (Journal of Surgical Sciences, 2026)
Objective: Despite (Snodgrass technique) surgical innovations of in 1994, hypospadias repair remains challenging due to persistent risks of postoperative complications. This study presents a comparative analysis with an excellent 12-year follow-up, evaluating the long-term efficacy, complication rates, and cosmetic outcomes of the modified Snodgrass procedure with a vascularized dartos flap versus the original Snodgrass technique for distal and mid penile hypospadias.Methods: This quasi-experimental study was conducted in the Department of Urology, Dhaka Medical College, and a Private Hospital, Dhaka, Bangladesh, between January 1, 2007, and December 31, 2008. A total of 64 patients aged 3–18 years with distal or mid penile hypospadias were enrolled. Group A underwent the modified Snodgrass urethroplasty with vascularized dartos flap wrap, while Group B underwent conventional Snodgrass urethroplasty. Follow-up assessments were scheduled at two weeks, one, three, and six months of time, and then annually for 12 years (until 2020). The evaluation approach included history, physical examination, urine testing, and uroflowmetry. An assessor who was blind to the procedure recorded every outcome. The rate of urethrocutaneous fistula is the main result in outcome measurements. Secondary consequences include cosmetic results (glans form and meatal configuration) and other issues (chronic chordee, flap sloughing, urethral stricture, and meatal stenosis).Results: The mean age was 5.4 ± 2.17 years in Group A and 7.6 ± 2.81 years in Group B. Complications were fewer in the modified technique group, with urethrocutaneous fistula developing in 6.25% of cases compared to 9.37% in the control group (p < 0.05). After a 12-year follow-up,, 93.75% of Group A patients achieved satisfactory urinary flow rates versus 84.37% in Group B. A normal conical glans with a vertical slit-like meatus was achieved in 84.37% of Group A versus 75% in Group B.Conclusion: The modified Snodgrass urethroplasty with vascularized dartos flap wrap yields superior cosmetic and functional outcomes with fewer complications. This technique is simple, reliable, and suitable for use in resource-constrained settings, and it should be considered the preferred approach for distal and mid penile hypospadias repair.Journal of Surgical Sciences 2022;26(2): 68-72